(untitled) (Scientific journal of the Fergana State University, 2025)
In the modern world, media technologies play a crucial role in the educational process, transforming traditional teaching methods and making them more accessible, interactive, and effective. This article examines the impact of media on learning, analyzes key digital tools used in education, and discusses the benefits and challenges of their integration. The study reviews academic literature and includes a survey conducted among teachers and students. The results indicate that media use enhances student motivation, fosters critical thinking, and improves knowledge retention. However, challenges such as information overload, digital inequality, and a lack of technical infrastructure were also identified. The article concludes with recommendations for the effective implementation of media in education and outlines future research directions in this field.